Evaluation of a combined approach of clinical skills training utilizing near-peers, in-campus faculty and clinicians: An innovative integrated model. (25th March 2016) - Zafar, Muhammad; Inayah, A'man Talal; Shareef, Mohammad Abrar; Aldalati, Alaa M.Z.; Afsar, Nasir Ali; Abu-Zaid, Ahmed; Zafar, Fatimah; Azouz, Haya Jamal
Abstract: Introduction: Training clinical skills is essential in medicine. Different models of clinical skills courses have been previously suggested. Here, we report an innovative approach adopted to train junior medical students in clinical skills in a multimodal fashion by near-peers, basic scientists with clinical background and senior clinicians. Methods: This quasi-experimental study was conducted at Alfaisal University College of Medicine at Riyadh. An electronic survey was conducted among year-2 and year-3 medical students seeking their perception about the (a) organization, (b) delivery, (c&d) self- and peer-assessment in clinical skills courses. Total 298 male and female medical students (91%), consisting of 164 from year 2 and 134 from year 3, participated by filling out a questionnaire (Cronbach's alpha 0.93). Results: Out of maximum five, the average ratings for the course were 3.81, 3.72, 3.67 and 3.73 in organization, delivery, self-evaluation and peer-assessment respectively, with no significant difference between both subgroups. The in-campus sessions rated higher than hospital sessions ( p < 0.001). As tutors, interns were rated higher than clinicians ( p < 0.001). The qualitative analysis suggested high satisfaction. Conclusions: The clinical skills course that was conducted in a multimodal fashion utilizing diverse tutors showed a positive attitude of students toward the organization and delivery of the course.